The Concept of Divine Oneness: A Synthesis Between Sufistic Tauhid and Mulla Sadra’s Philosophy of Wujud - Lutfi, Muhammad; Riyadi, Abdul Kadir (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2024)
This article discusses the relationship between Mulla Sadra's philosophy of existence and the sufistic concept of monotheism. Tauhid as an Islamic paradigm can be seen from several levels, including the belief that there is no God but Allah; experience and witness to the Oneness of Allah; and the philosophical construction of experience and witness to the Oneness of Allah. Tauhid in the first point reflects the general theological view, while the second and third points reflect the Sufism paradigm. And according to the theologians, the philosophical construction of the Oneness of God, which is called wahdah al-wujud, among other things, has come out of the Islamic creed. At that point, Mulla Sadra can become a strategic bridge because he synthesizes various previous philosophies into a distinctive philosophical system. From the building of his philosophy, Sadra has three important parts that talk about the philosophy of Being: asalah al-wujud, wahdah al- wujud, and tashqiq al- wujud. This philosophy of being will be dissected through the sufistic paradigm to provide an answer whether sufistic monotheism has violated the Islamic creed. The approach used is descriptiveanalysis. The main finding is that Mulla Sadra's philosophy of being is still related to monotheism, especially sufi monotheism, because Sadra does not deny Allah as the One Supreme Being, nor does he carry the idea of mono-existentialism like Ibn Arabi, which is the main goal of the theologians' criticism